Carica papaya Leaves Juice Significantly Accelerates the Rate of Increase in Platelet Count among Patients with Dengue Fever and Dengue Haemorrhagic Fever. (11th April 2013) - Subenthiran, Soobitha; Choon, Tan Chwee; Cheong, Kee Chee; Thayan, Ravindran; Teck, Mok Boon; Muniandy, Prem Kumar; Afzan, Adlin; Abdullah, Noor Rain; Ismail, Zakiah
Abstract : The study was conducted to investigate the platelet increasing property of Carica papaya leaves juice (CPLJ) in patients with dengue fever (DF). An open labeled randomized controlled trial was carried out on 228 patients with DF and dengue haemorrhagic fever (DHF). Approximately half the patients received the juice, for 3 consecutive days while the others remained as controls and received the standard management. Their full blood count was monitored 8 hours for 48 hours. Gene expression studies were conducted on the ALOX 12 and PTAFR genes. The mean increase in platelet counts were compared in both groups using repeated measure ANCOVA. There was a significant increase in mean platelet count observed in the intervention group (P < 0.001 ) but not in the control group 40 hours since the first dose of CPLJ. Comparison of mean platelet count between intervention and control group showed that mean platelet count in intervention group was significantly higher than control group after 40 and 48 hours of admission (P < 0.01 ). The ALOX 12 (FC = 15.00) and PTAFR (FC = 13.42) genes were highly expressed among those on the juice. It was concluded that CPLJ does significantly increase the platelet count in patients with DF and DHF.